2016
DOI: 10.1016/j.celrep.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Severe Malaria Infections Impair Germinal Center Responses by Inhibiting T Follicular Helper Cell Differentiation

Abstract: Naturally acquired immunity to malaria develops only after years of repeated exposure to Plasmodium parasites. Despite the key role antibodies play in protection, the cellular processes underlying the slow acquisition of immunity remain unknown. Using mouse models, we show that severe malaria infection inhibits the establishment of germinal centers (GCs) in the spleen. We demonstrate that infection induces high frequencies of T follicular helper (Tfh) cell precursors but results in impaired Tfh cell differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
228
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(252 citation statements)
references
References 49 publications
21
228
2
1
Order By: Relevance
“…These would be interesting targets to explore in this system as well. Indeed, extended expression of type I IFN or IFN-␥ has recently been shown to inhibit germinal center production in chronic P. berghei and P. yoelii infections (40,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These would be interesting targets to explore in this system as well. Indeed, extended expression of type I IFN or IFN-␥ has recently been shown to inhibit germinal center production in chronic P. berghei and P. yoelii infections (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, CD4 T cell exhaustion has not been well documented in any situation. Instead, there is a concerted change in the cytokine profile of chronically stimulated T cells in LCMV and malaria away from Th1 or Tfh commitment (40,41,(47)(48)(49), suggesting that the effect of chronic infection on CD4 T cells is different than that on CD8 cells. On the other hand, PD-1 is expressed on human T cells in P. falciparum infections (44), and T cell proliferation is reduced in areas of continuous exposure to P. falciparum compared to those with successful control programs (21).…”
Section: Discussionmentioning
confidence: 99%
“…We have now extended those observations by providing evidence that a lack of CXCL10 during infection results in significantly increased numbers of CXCR3 + CD4 + Tfh cells in the spleen. We have recently found that P. berghei ANKA infection induces primarily a population of Tfh cell precursors, which, despite normal Bcl-6 and IL-21 expression, display low levels of PD-1 and CXCR5 and coexpress Th1-associated molecules such as T-bet and CXCR3 (31). Although these cells do not appear to efficiently support GC responses, work by others (45) suggested that they are required to provide help for the induction of extrafollicular Ab responses.…”
Section: Discussionmentioning
confidence: 99%
“…CPS-CQimmunized individuals reacted preferentially to 84 preerythrocytic Ags, while the Kenyan participants reacted preferentially to 238 blood-stage Ags. Both groups reacted to about 90 cross-stage Ags (53,54). It is possible that different antigenic profiles contribute to the differences in immune sustainability or/and the CQ drug may modify the T and B cell memory responses.…”
Section: Malaria Vaccinesmentioning
confidence: 99%